2022
DOI: 10.1080/15502783.2022.2100718
|View full text |Cite
|
Sign up to set email alerts
|

Seven-month wintertime supplementation of 1200 IU vitamin D has no effect on hand grip strength in young, physically active males: A randomized, controlled study

Abstract: Background There has been a growing interest in the role of vitamin D for the well-being and physical performance of humans under heavy training such as conscripts in military service; however, there is a lack of long-term supplementation studies performed on members of this type of young, physically active, male population. The hypothesis of the study was that vitamin D supplementation during wintertime will decrease the prevalence of critically low vitamin D blood serum levels and increase hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…Thus, no spectacular changes in MMA athletes were observed. It was also shown that seven months of vitamin D 3 supplementation (1200 IU daily) had no effect on calcium, parathormone, cortisol, and testosterone blood concentrations, as well as hand grip strength among Estonian soldiers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no spectacular changes in MMA athletes were observed. It was also shown that seven months of vitamin D 3 supplementation (1200 IU daily) had no effect on calcium, parathormone, cortisol, and testosterone blood concentrations, as well as hand grip strength among Estonian soldiers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary variable of the study was the level of 25(OH)D in the serum. Based on the findings in the study of Rips et al [ 36 ], a difference of 20 nmol/L between the study groups was considered meaningful to measure. For example, for an SD of 25 nmol/L, 26 participants would be needed in each group to reach a power of 80%.…”
Section: Methodsmentioning
confidence: 99%
“…In an Estonian‐population‐based study, Kull et al [ 21 ] found mean winter serum 25(OH)D levels of 43.7 nmol/L. In a randomized controlled study (RCT) by Rips et al [ 36 ], the lowest mean 25(OH)D value of 21.9 nmol/L was found in March in a placebo group of young men undergoing military service. Another Estonian study found critically low vitamin D values (<25 nmol/L) in 36% and deficiency (<50 nmol/L) in 92% of young conscripts in the spring season [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations